Communication modernization on the fishermen of indigenous tribe Akit in Rupat Island, Riau - Ridar Hendri; Eni Yulinda; Clara Yolandika (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
This study aims to analyze the development of communication modernization among fishermen from the Akit tribe in North Rupat. Rupat Island, Bengkalis Regency, Riau Province. The study used a qualitative method involving 17 informants. Data collection used in-depth interview techniques with three fisherman owners (tekong), eight fisherman workers (crews), and an exporter; and focus discussion groups (FGD) with a prominent fisherman, a fisherman owner, two fisherman workers, and an officer from the Fish Landing Base Technical Implementation Unit. The data were analyzed descriptively. This study found that fishermen from the Akit Tribe in Rupat Utara totaled 763 people, consisting of owner fishermen (38.68%) and labor fishermen (61.32%). Most fishermen use gill nets measuring 500 meters to catch fish (95%). Their total fish production averages 1.61 million tons per year, including parang fish (Chirocentrus dorab), senagin (Eleutheronema tetradactylum), senohong (Leptomelanosoma indicum), kurau (Polydactyus octonemus), red snapper (Lutjanus campechanus), and mackerel (Scomberomorus sp.). Almost all fishermen's fish are exported to Malaysia (80%). Furthermore, we found that most of the fishermen from the Akit Tribe still have low education (95%), but have implemented modern communication patterns. This can be seen in the changes in the communication tools they use, from traditional to modern. Since 1990, they have been using HT (handy talky) to communicate among fishermen and with exporters (tauke). Furthermore, in 2015, they already used smartphones and internet-based communication media, especially WhatsApp. To obtain information related to fishing efforts, they use the Google Maps application (to find fish), social media YouTube, and online media published locally (Riau) such as riaupos.co, goriau.com, and tribunpekanbaru.com. They use social media and online media while resting on the ship before lifting the fishing nets onto the ship. The material they communicate includes information about the types of fish caught, the price of fish, the number of requests for fish, the obstacles faced when fishing in the middle of the sea, and so on. Most fishermen of the Akit Tribe go to the sea for 2–9 days per fishing trip (5%). The smooth internet access on Rupat Island is due to the availability of 19 BTS (Base Transceiver Station) towers, making it easier for Akit fishermen to communicate.